Fox at night - Tabor, Corey R. (New York, NY : Balzer + Bray, an imprint of HarperCollins Publishers, 2021)
Fox is up late in the night. There are shadows and noises everywhere. Fox is sure the night is full of monsters!
Keywords: Foxes -- Juvenile fiction; Fear -- Juvenile fiction; Friendship -- Juvenile fiction; Monsters -- Juvenile fiction; Animals -- Juvenile fiction; Night -- Juvenile fiction; Nocturnal animals -- Juvenile fiction; Picture books; Readers (Publications)